Evaluasi dan Rekonstruksi Soal Asesmen Sumatif Bahasa Indonesia Berdasarkan Taksonomi Bloom di Sekolah Menengah Pertama: Evaluation and Reconstruction of Indonesian Language Summative Assessment Questions Based on Bloom’s Taxonomy in Junior High School - Ramadhanti, Gisella Orlanova; Naryatmojo, Deby Luriawati; Wagiran, Wagiran (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the distribution of cognitive levels in Indonesian language summative assessment questions for grades VII, VIII, and IX at SMP Negeri 2 Ciledug and to reconstruct Lower Order Thinking Skills (LOTS) questions into Higher Order Thinking Skills (HOTS) questions based on Anderson and Krathwohl’s Revised Bloom’s Taxonomy. This study employed a mixed-methods approach combining descriptive quantitative and qualitative analyses. The data consisted of 150 Indonesian language summative assessment items analyzed according to cognitive levels C1–C6. The results showed that the questions were dominated by the remembering (C1) and understanding (C2) levels. In grades VII and VIII, all questions were categorized as LOTS, while in grade IX, 10% of the questions reached the analyzing level (C4). No questions were found at the evaluating (C5) and creating (C6) levels. The reconstruction results indicated that LOTS questions can be developed into HOTS questions through enriched stimuli, authentic contexts, and higher cognitive demands. This study provides an alternative framework for developing Indonesian language assessments that are more oriented toward higher-order thinking skills in accordance with the Merdeka Curriculum.